2019
DOI: 10.1128/msphere.00354-19
|View full text |Cite
|
Sign up to set email alerts
|

Screening Mycobacterium tuberculosis Secreted Proteins Identifies Mpt64 as a Eukaryotic Membrane-Binding Bacterial Effector

Abstract: Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, is one of the most successful human pathogens. One reason for its success is that Mtb can reside within host macrophages, a cell type that normally functions to phagocytose and destroy infectious bacteria. However, Mtb is able to evade macrophage defenses in order to survive for prolonged periods of time. Many intracellular pathogens secrete virulence factors targeting host membranes and organelles to remodel their intracellular environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 150 publications
1
18
0
Order By: Relevance
“…yEGFP-SopF was produced at equivalent levels in all yeast strains upon galactose induction (S3C Fig). Notably, the steady-state subcellular localization of SopF in yeast (internal membrane sites; Fig 3A, S3B Fig) and mammalian cells (plasma membrane; Figs 2C and 3B) differed, similar to what has previously been reported for some secreted bacterial proteins [58,65]. This may be a consequence of imaging in live (yeast) versus formaldehyde-fixed (HeLa) cells.…”
Section: Resultssupporting
confidence: 78%
“…yEGFP-SopF was produced at equivalent levels in all yeast strains upon galactose induction (S3C Fig). Notably, the steady-state subcellular localization of SopF in yeast (internal membrane sites; Fig 3A, S3B Fig) and mammalian cells (plasma membrane; Figs 2C and 3B) differed, similar to what has previously been reported for some secreted bacterial proteins [58,65]. This may be a consequence of imaging in live (yeast) versus formaldehyde-fixed (HeLa) cells.…”
Section: Resultssupporting
confidence: 78%
“…This suggests that M. tuberculosis inhibits Perk signaling to delay apoptosis of the host cell thereby promoting bacterial replication. The Mpt64 protein ( Rv1980c ) has also been shown to localize to the ER to inhibit CHOP expression [ 39 ], although whether it inhibits upstream phosphorylation of Perk or eIF2α was not tested.…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacteria have several protein secretion systems including type VII secretion system for their housekeeping growth and modulation of infected host immune system (Ligon et al, 2012). By comparison with secreted proteins of M. tuberculosis reported previously (Penn et al, 2018;Stamm et al, 2019), we found that twenty-two M. tuberculosis proteins among 614 detected ones were indicated to be presumably secreted proteins (Supplementary Figure S8 and Supplementary Table S4). Six of these proteins are Mce family proteins which are secreted or on the cell surface to facilitate host cell entry (Chitale et al, 2001;Saini et al, 2008;Zhang et al, 2018).…”
Section: Detection Of Mycobacterial Proteins In Granulomatous Lesionsmentioning
confidence: 70%
“…FIGURE S8 | Venn diagram illustrating the number of proteins in common among the present (This_study) and previously reported studies (Penn et al, 2018;Stamm et al, 2019). The gene lists for Stamm_2019 and Penn_2018 were reported by Penn et al (2018) and Stamm et al (2019). TABLE S1 | Excel file of the raw and imputed data of all proteomic analyses for identification of human, M. tuberculosis, and MAH proteins in mycobacterial granulomatous lesions.…”
Section: Resultsmentioning
confidence: 97%